PERENCANAAN KEUANGAN JANGKA PANJANG UNTUK MEMUTUSKAN SIKLUS GENERASI SANDWICH - Ujang Kusnaedi; Nizar Zulkarnain; Rasmawati AR (JURNAL ILMIAH EDUNOMIKA, 2025)
The sandwich generation phenomenon, wherein individuals simultaneously support both elderly parents and dependent children, has emerged as an increasingly critical issue amidst Indonesia’s complex socioeconomic landscape. This study aims to identify the financial literacy level of the sandwich generation and analyze its impact on long-term financial planning practices. A descriptive quantitative approach was employed, involving 100 respondents aged 30–50 years residing in the Greater Jakarta area (Jabodetabek) who met the criteria for multigenerational financial responsibilities. Data were collected through a closed-ended Likert-scale questionnaire and semi-structured interviews, and analyzed using descriptive statistics, Pearson correlation, and simple linear regression with SPSS version 25. The findings revealed that financial literacy among respondents was at a moderate level, but remained insufficient in terms of long-term financial products. A positive and significant relationship was found between financial literacy and financial planning (r = 0.514; p < 0.05), with financial literacy also having a significant effect on financial planning practices (R² = 0.264). These results Keywords : Sandwich generation, financial literacy, financial planning, multigenerational burden, financial education, Jabodetabek.